USE OF THE CALGARY FAMILY ASSESSMENT MODEL IN STRUCTURAL, DEVELOPMENTAL AND FUNCTIONAL ASSESSMENT OF THE FAMILY OF MASTECTOMIZED WOMEN WITH BREAST CANCER - Patrícia Peres de Oliveira; Lorena Nogueira Maia; Mariella de Souza Resende; Rúbia Sousa Macedo; Andrea Bezerra Rodrigues; Maria Ísis Freire de Aguiar (Universidade Federal do Paraná, 2015)
The present study aimed to assess the structure, development and functionality of the family of women with breast cancer who underwent mastectomy. It is a qualitative study based on the Calgary Family Assessment Model and case study methodology was used. The data were collected from two families in May-September 2014, through a previously designed instrument. One of the families was a nuclear family formed by the biological parents and their three daughters, and the other family was extended, consisting of two sisters, both mastectomized, and their respective children. The use of the family assessment model provided knowledge on aspects related to the structure, functioning and development of the two families that interfere, impair or favor the adequate provision of daily care.In conclusion, this study made it possible to use a family assessment model that can interfere, impair or favor the adequate provision of daily care to the patients.